The Development of AKSI (Aktualisasi Siswa) Learning Model to Improve Higher Order Thinking Skills of Natural Science in Junior High School - Rohmah, Indi Ghozirur; Supeno, Supeno; Hariani, Sulifah Aprilya (Universitas PGRI Semarang, 2023)
This research aims to develop a valid, practical, and effective Aksi learning model. The research method used is development research with adaptation of Thiagarajan development steps. Based on the results of the needs analysis on the questionnaire given to 15 science teachers in several regions in East Java, educators stated that the students' higher-order thinking skills were not optimal. Higher-order thinking skills show that students have C4, C5, and C6 knowledge abilities. Based on these data it is necessary to develop a learning model that fits the needs, the Aksi learning model. This research aims to develop a valid, practical, and effective Aksi learning model. The research method used is development research with an adaptation of the development steps developed by Thiagarajan. The 4D development model is carried out with 4 research stages namely Define, Design, Develop, and Disseminate. Aksi learning model development research produces data in the form of valid, practical, and effective values. The Aksi learning model has a validity score of 88.10% in the very valid category. The practicality value of the observation of the implementation is 89.24% in the very practical category, the teacher response test was 89,38% in the very practical category, and the student response test was 84.12% in the very practical category. The value of the model's effectiveness is to get an N-gain score for high-level thinking skills, which is 0.7 in the high category.